Correlates of sedentary behaviors among adults from eastern Poland - Stelmach, Marian Jan; Baj-Korpak, Joanna; Niźnikowska, Ewelina Anna; Bergier, Barbara; Bergier, Michał; Tomczyszyn, Dorota; Rocha, Paulo (Frontiers in Public Health, 2025)
BackgroundResearch on sedentary behaviors in the Polish population using objective methods, such as accelerometry, remains limited. These behaviors, defined as time spent on passive activities or minimal physical effort, require further investigation. This study aimed to identify socio-demographic and health-related correlates of sedentary behaviors in a cohort of adults from eastern Poland.MethodsA total of 173 adults from eastern Poland participated in the study. Socio-demographic data were collected using the EHIS (wave 3) questionnaire. Movement behaviors were monitored for 7 days using a triaxial accelerometer. Statistical analyses focused on the prevalence of sedentary behaviors (SB) and correlations for qualitative and quantitative variables for two- and multiple-group comparisons. The final stage involved regression models explaining SB and step count per day.ResultsParticipants spent an average of 8 h and 34 min per day in sedentary behaviors, with a mean daily step count exceeding 8,000. Self-rated health, gender, employment status, and marital status were the strongest correlates of sedentary behavior. Linear regression analysis showed that in the case of step count per day, employment status is a statistically significant predictor explaining 11.8% of the variance.ConclusionThe obtained findings underscore the necessity for further research to explore the causal relationships of the prevalence of sedentary behaviors, particularly among socially and professionally excluded individuals.